Solve for a 2(a-6)=3a

Math
2(a-6)=3a
Simplify 2(a-6).
Tap for more steps…
Apply the distributive property.
2a+2⋅-6=3a
Multiply 2 by -6.
2a-12=3a
2a-12=3a
Move all terms containing a to the left side of the equation.
Tap for more steps…
Subtract 3a from both sides of the equation.
2a-12-3a=0
Subtract 3a from 2a.
-a-12=0
-a-12=0
Add 12 to both sides of the equation.
-a=12
Multiply each term in -a=12 by -1
Tap for more steps…
Multiply each term in -a=12 by -1.
(-a)⋅-1=12⋅-1
Multiply (-a)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1a=12⋅-1
Multiply a by 1.
a=12⋅-1
a=12⋅-1
Multiply 12 by -1.
a=-12
a=-12
Solve for a 2(a-6)=3a

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top